2013
DOI: 10.1186/1472-6882-13-151
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial activity and rutin identification of honey produced by the stingless bee Melipona compressipes manaosensis and commercial honey

Abstract: BackgroundHoney has been identified as a potential alternative to the widespread use of antibiotics, which are of significant concern considering the emergence of resistant bacteria. In this context, this study aimed to evaluate the antimicrobial activity of honey samples produced by a stingless bee species and by Apis sp. against pathogenic bacteria, as well as to identify the presence of phenolic compounds.MethodsHoney samples from the stingless bee M. compressipes manaosensis were collected twice, during th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
38
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(41 citation statements)
references
References 32 publications
2
38
0
1
Order By: Relevance
“…The antimicrobial activity of stingless bee honey was validated by using the Kirby-Bauer antibiotic test, the agar dilution test, broth microdilution, and time-kill viability assays [10,64,65]. This study was supported by researchers from Brazil where they found that stingless bee honey has the ability to inhibit the growth of gram-positive and gram-negative bacteria [66]. A unique feature of stingless bee honey is that it is stored in cerumen pots made of wax and propolis.…”
Section: Antimicrobial Role Of Stingless Bee Honeymentioning
confidence: 94%
“…The antimicrobial activity of stingless bee honey was validated by using the Kirby-Bauer antibiotic test, the agar dilution test, broth microdilution, and time-kill viability assays [10,64,65]. This study was supported by researchers from Brazil where they found that stingless bee honey has the ability to inhibit the growth of gram-positive and gram-negative bacteria [66]. A unique feature of stingless bee honey is that it is stored in cerumen pots made of wax and propolis.…”
Section: Antimicrobial Role Of Stingless Bee Honeymentioning
confidence: 94%
“…In a study by Pimentel (2013), honey samples collected from the stingless bee Melipona compressipes manaosensis in Manaus, Amazonas, Brazil, were active against E. coli, S. aureus, Proteus vulgaris and Klebsiella species 18 . Using agar well diffusion assays it was demonstrated that honey collected during the rainy season inhibited the growth of E. coli only in undiluted forms, whilst, honey collected during the dry season inhibited the growth of E. coli, S. aureus and a range of other microbes at much more diluted concentrations.…”
Section: Antimicrobial Properties Of Manuka Honey Against Skin Relevamentioning
confidence: 99%
“…Methods that have been used to evaluate the inhibitory activity of honey against bacterial growth include agar diffusion and dilution methods (Pimentel et al, 2013;Hermawati et al, 2016). The dilution method is performed a solution of antimicrobial agents in a serial of concentration added into the broth media that has been inoculated with a test bacteria, then dishes containing the test media inoculated by a test bacteria and the test solution are incubated at 37 °C for 24-48 (Lourenço, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Diameter of the inhibitory zone is directly proportional to the antibacterial activity of the substance. The wider the diameter of inhibitory zone means the stronger antibacterial activity (Brooks et al, 2013;Pimentel et al, 2013).…”
Section: Introductionmentioning
confidence: 99%